2015
DOI: 10.3906/biy-1411-88
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical and histoanatomical response of some woodyspecies to anthropic impact in Suceava County, Romania

Abstract: + OH -) reactions, generating ROS. Other metals with redox capacity (cadmium -Cd, zinc -Zn, and mercury -Hg) are able to cause metabolic imbalances, destroying the antioxidant potential of the cell through the inhibition of oxidative stress enzymes and increasing the production of oxygen radicals (Keunen et al., 2011).Anthropogenic S mining activity carried out in the Călimani Mountains resulted in extremely low maintenance of soil pH due to the presence of S and its oxidation reactions (sulfates over the limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Therefore, this anthropogenic influence exceeds permissible value of heavy metal content in soils caused major disruptions to their quality. The analysis of other authors of biochemical properties of the species from different polluted areas of Suceava County showed that the range of antioxidant responses to the pollution conditions at Tarnita and other sites was different, depending on the type of pollutant interference in the environment [9]. Thus, the metal ions resulting from polymetallic sulfide alteration in Tarnita were able to inhibit the activity of SOD in Picea abies L.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this anthropogenic influence exceeds permissible value of heavy metal content in soils caused major disruptions to their quality. The analysis of other authors of biochemical properties of the species from different polluted areas of Suceava County showed that the range of antioxidant responses to the pollution conditions at Tarnita and other sites was different, depending on the type of pollutant interference in the environment [9]. Thus, the metal ions resulting from polymetallic sulfide alteration in Tarnita were able to inhibit the activity of SOD in Picea abies L.…”
Section: Samplingmentioning
confidence: 99%
“…Environmental pollution with heavy metals around the barite closed mine of Tarniþa does represent high risks to the public health in Eastern Carpathians, being also an intensively studied issue [6][7][8][9][10][11][12]. There are also some other similarly contaminated areas in Romania such as Copºa Micã, Baia Mare and Zlatna [13][14][15][16][17].…”
mentioning
confidence: 99%